Hubungan Pengetahuan, Sikap, dan Perilaku Ibu Hamil Terhadap Kehamilan Risiko Tinggi - Muliatul Jannah; Endang Surani; Rahayu Sekar Dewi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The Maternal Mortality Rate (MMR) in Indonesia is still relatively high. This problem cannot be separated from the high-risk pregnancies faced by pregnant women. The impact of high-risk pregnancies include miscarriage, premature, bleeding, fetal death, increasing births with surgery. Factors that influence high-risk pregnancies include knowledge, attitudes, and behavior of pregnant women. Thus, this study aims to determine the relationship between knowledge, attitudes, and behavior of pregnant women on high-risk pregnancies. This study applies a literature review (literature review) as a research design for journals that have been selected according to the topics in this study. The journals obtained are 10 journals in the last 5 years that are relevant to the variables in this study. The results of this study indicate that there is a relationship between knowledge, attitudes, and behavior of pregnant women towards high-risk pregnancies. Acquisition of knowledge cannot be separated from the role of health facilities and medical personnel who are experts in handling childbirth. Whereas knowledge shapes behavior and attitudes that raise awareness and will eventually cause people to behave and act in accordance with the knowledge they have. Good behavior is obtained from good knowledge as well. Meanwhile, negative behavior results from a lack of knowledge. The better the knowledge, attitude, and behavior of pregnant women during pregnancy to delivery, the lower the high-risk pregnancy for pregnant women.